Spin Dependent Tunneling through a Nanometer-thick Square Barrier Based on Zinc-blende Structure Material - Adi Bagus Suryamas; Mikrajuddin Abdullah; Khairurrijal Khairurrijal (Indonesian Journal of Physics, 2006)
Spin dependent tunneling through a nanometer thick square barrier based on zinc- blende structure material has a great deal of attention due to its potential application in spintronics devices. An analytic expression of the transmittance T of an electron with spin polarization has been derived by adding the Dresselhauss term to the commonly used Hamiltonian and solving the Schrödinger equation. Solutions of the Schrödinger equation give two states referred as the “up” or “+” and “down or “-” spin states. It was found that the “up” and the “down” state transmittances are asymmetric to the axis at the normal incidence (θ=0o). Moreover, at the normal incidence the transmittances are equal because the parallel wave vectors are zero and not the highest. In addition, it was also found the relation T+(θ)= T-(-θ) due to the anisotropic properties of heterostructure materials.